Teaching and learning Chinese in global contexts : multimodality and literacy in the new media age - Tsung, Linda T. H., 1953-; Cruickshank, Ken (Continuum, 2011)
Although there is an extensive literature on the teaching of English as a Second or Other Language, there is very little published research on the teaching or learning of Chinese in similar contexts. This book is the first to bring together research into the teaching and learning of Chinese as a foreign language to non-native speakers, as a second language to minority groups and as a heritage/community language in the diaspora. The volume showcases the contribution of researchers working in such areas as language teaching and learning, policy development, language assessment, language develop.